Minimum dietary diversity and its determinants among lactating mothers in five Sub-Saharan African countries: A multilevel analysis - Alebachew Ferede Zegeye; Tadesse Tarik Tamir; Desale Bihonegn Asmamaw; Desalegn Anmut Bitew; Elsa Awoke Fentie; Bewuketu Terefe; Rahel Mulatie Anteneh; Lemlem Daniel Baffa; Misganaw Guadie Tiruneh; Kaleb Assegid Demissie; Tadele Biresaw Belachew; Wubshet D. Negash; et al. (PLoS ONE, 2025)
Background Ensuring minimum dietary diversity is crucial for lactating mothers. It allows them to consume a variety of foods from different groups, meeting their nutritional needs and supporting maternal and infant health. Despite the global impact of undernutrition and micronutrient deficiencies, the prevalence and determinants of minimum dietary diversity during lactation remain poorly recognized in developing countries. This research aims to assess minimum dietary diversity and its determinants among lactating mothers in five Sub-Saharan African countries. Methods Data from the most recent Demographic and Health Surveys, which covered five Sub-Saharan African countries between 2021 and 2023, were used to execute secondary data analysis. This study included 19,917 lactating mothers in total. Using a multilevel mixed-effects logistic regression model, the variables associated to the minimum dietary diversity were established. Significant factors associated with the minimum dietary diversity were found at p-values < 0.05. The adjusted odds ratio and 95% CI were used to interpret the result. The model with the highest loglikelihood ratio and lowest deviance was declared to be the best fit. Results The magnitude of minimum dietary diversity among lactating mothers in Burkina Faso, Ghana, Kenya, Mozambique, and Tanzania was 25.66% (95% CI: 24.47, 25.75). Factors such as secondary and above educational level (AOR =  1.38, 95% CI: 1.18, 1.61), employed mothers (AOR =  1.40, 95% CI: 1.26, 1.56), distance which was not a big problem to access health facilities (AOR =  1.35, 95% CI: 1.21, 1.51), health facility delivery (AOR =  1.25, 95% CI: 1.08, 1.45), rich wealth status (AOR =  1.86, 95% CI: 1.60, 2.17), high community ANC utilization (AOR =  1.18, 95% CI: 1.04, 1.35), and reside in Ghana (AOR =  4.21, 95% CI: 3.60, 4.94) had higher odds of minimum dietary diversity. Conclusions This study reveals that lactating mothers have low dietary diversity. Both community-level and individual-level factors impact this diversity. Consequently, health ministries in Burkina Faso, Kenya, Ghana, Mozambique, and Tanzania should prioritize women who underutilize antenatal services and those without formal education when designing strategies and policies.